A comparative analysis of service quality among ECOWAS seaports. (July 2020) - Sakyi, Daniel
Abstract: Customers' expectations and perceptions about service quality continue to remain essential for the growth and survival of firms. In the case of seaports, these expectations and perceptions cannot be overemphasized given that, seaports are at the heart of international trade. Considering the role of trade in increasing economic and social welfare outcomes of countries, improving trade facilitation through enhanced service quality at seaports remain very essential. Notwithstanding the above, it is startling to note that very little is known about service quality across Economic Community of West African States (ECOWAS) seaports. This study therefore provides comparative analyses of service quality at selected ECOWAS seaports using the gap score technique of the service quality (SERVQUAL) model. The study reveals that in general, all the selected seaports studied have poor service quality. This outcome calls for instituting effective measures towards enhancing service quality at ECOWAS seaports. Highlights: Customers' expectations and perceptions about service quality remain essential for the growth and survival of firms Seaports expectations and perceptions cannot be overemphasized since they are at the heart of international trade A comparative analysis of customers' expectations and perceptions of service quality at ECOWAS seaports is investigated Generally speaking, all the selected seaports have low service quality Effective measures toward enhancing service quality at ECOWAS seaports are suggested